Osteocyte‐Secreted Wnt Signaling Inhibitor Sclerostin Contributes to Beige Adipogenesis in Peripheral Fat Depots. (5th January 2017) - Fulzele, Keertik; Lai, Forest; Dedic, Christopher; Saini, Vaibhav; Uda, Yuhei; Shi, Chao; Tuck, Padrig; Aronson, Jenna L; Liu, Xiaolong; Spatz, Jordan M; Wein, Marc N; Divieti Pajevic, Paola
ABSTRACT: Cells of the osteoblast lineage are increasingly identified as participants in whole‐body metabolism by primarily targeting pancreatic insulin secretion or consuming energy. Osteocytes, the most abundant bone cells, secrete a Wnt‐signaling inhibitor called sclerostin. Here we examined three mouse models expressing high sclerostin levels, achieved through constitutive or inducible loss of the stimulatory subunit of G‐proteins (Gsα in mature osteoblasts and/or osteocytes). These mice showed progressive loss of white adipose tissue (WAT) with tendency toward increased energy expenditure but no changes in glucose or insulin metabolism. Interestingly beige adipocytes were increased extensively in both gonadal and inguinal WAT and had reduced canonical β‐catenin signaling. To determine if sclerostin directly contributes to the increased beige adipogenesis, we engineered an osteocytic cell line lacking Gsα which has high sclerostin secretion. Conditioned media from these cells significantly increased expression of UCP1 in primary adipocytes, and this effect was partially reduced after depletion of sclerostin from the conditioned media. Similarly, treatment of Gsα‐deficient animals with sclerostin‐neutralizing antibody partially reduced the increased UCP1 expression in WAT. Moreover, direct treatment of sclerostin to wild‐type mice significantly increased UCP1 expression in WAT. These results show that osteocytes and/or osteoblasts secrete factors regulating beige adipogenesis, at least in part, through the Wnt‐signaling inhibitor sclerostin. Further studies are needed to assess metabolic effects of sclerostin on adipocytes and other metabolic tissues. © 2016 American Society for Bone and Mineral Research.